EKSPRESI GEN PROTEIN SELUBUNG TOMATO INFECTIOUS CHLOROSIS VIRUS PADA ESCHERICHIA COLI - Fitrianingrum Kurniawati; Gede Suastika; Giyanto . (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2015)
Expression of tomato infectious chlorosis virus coat protein gene on Escherichia coli. Tomato infectious chlorosis virus (TICV) is the causal agent of chlorotic disease of tomato. Detection of TICV can be carried out by RT-PCR and serological test. Titer of TICV in plant tissue is very low because TICV is limited to phloem. Serological detection of TICV requires antiserum which is not available in Indonesia. Producing antibody through cloning and coat protein gene (TICV CP gene) expression is a promising approach in producing antiserum. The objective of this study was to express TICV CP gene as antigen for antiserum production. TICV CP gene was amplified using RT-PCR from total RNA extracted from TICV infected leaves collected from Cipanas, Cianjur, West Java. The amplified CP gene was then sequenced and sub-cloned into pET 21b expression vector, transformed into Escherichia coli strain BL21 DE3(pLysS) and induced expression using IPTG 1 mM overnight at 37 Â°C. CP that contains 6xhistag was purified using NiNTAspin column and then confirmed by SDS-PAGE. The size of TICV CP gene was 750 bp and the gene was expressed on pET 21 b vector and SDS-PAGE showed a 29 kDa band.